Pathogenic Mechanisms of Vaccine-Induced Immune Thrombotic Thrombocytopenia in People Receiving Anti-COVID-19 Adenoviral-Based Vaccines: A Proposal - Azzarone, Bruno; Veneziani, Irene; Moretta, Lorenzo; Maggi, Enrico (Frontiers in Immunology, 2021)
VITT is a rare, life-threatening syndrome characterized by thrombotic symptoms in combination with thrombocytopenia, which may occur in individuals receiving the first administration of adenoviral non replicating vectors (AVV) anti Covid19 vaccines. Vaccine-induced immune thrombotic thrombocytopenia (VITT) is characterized by high levels of serum IgG that bind PF4/polyanion complexes, thus triggering platelet activation. Therefore, identification of the fine pathophysiological mechanism by which vaccine components trigger platelet activation is mandatory. Herein, we propose a multistep mechanism involving both the AVV and the neo-synthetized Spike protein. The former can: i) spread rapidly into blood stream, ii), promote the early production of high levels of IL-6, iii) interact with erythrocytes, platelets, mast cells and endothelia, iv) favor the presence of extracellular DNA at the site of injection, v) activate platelets and mast cells to release PF4 and heparin. Moreover, AVV infection of mast cells may trigger aberrant inflammatory and immune responses in people affected by the mast cell activation syndrome (MCAS). The pre-existence of natural antibodies binding PF4/heparin complexes may amplify platelet activation and thrombotic events. Finally, neosynthesized Covid 19 Spike protein interacting with its ACE2 receptor on endothelia, platelets and leucocyte may trigger further thrombotic events unleashing the WITT syndrome.